Daylight photodynamic therapy with methyl aminolevulinate cream as a convenient, similarly effective, nearly painless alternative to conventional photodynamic therapy in actinic keratosis treatment: a randomized controlled trial. (20th October 2014) - Rubel, D.M.; Spelman, L.; Murrell, D.F.; See, J.‐A.; Hewitt, D.; Foley, P.; Bosc, C.; Kerob, D.; Kerrouche, N.; Wulf, H.C.; Shumack, S.
Summary: Background: Daylight photodynamic therapy (DL‐PDT) of actinic keratosis (AK) has shown preliminary efficacy and safety results comparable to conventional photodynamic therapy (c‐PDT), using methyl aminolevulinate (MAL) cream. Objectives: To demonstrate the efficacy and safety of DL‐PDT vs. c‐PDT in treating mild facial/scalp AK. Materials and methods: This 24‐week randomized, controlled, investigator‐blinded, multicentre, intra‐individual efficacy (non‐inferiority) and safety (superiority regarding pain) study enrolled 100 subjects. AKs on the face/scalp were treated once, with DL‐PDT on one side and c‐PDT on the contralateral side. Primary end points for DL‐PDT at week 12 were efficacy [non‐inferiority regarding complete lesion response (mild AK)] and safety (superiority regarding subject's assessment of pain). Lesions with complete response 12 weeks after one treatment session were followed until week 24. The safety evaluation included incidence of adverse events. Subject satisfaction was classified using a questionnaire. Results: At week 12, the complete lesion response rate with DL‐PDT was non‐inferior to c‐PDT (89·2% vs. 92·8%, respectively; 95% confidence interval −6·8 to −0·3), confirmed by intention‐to‐treat analysis. Additionally, regardless of the treatment used, 96% of mild lesions were maintained in complete response 24 weeks after the PDT session. For DL‐PDT, subject‐reported pain was significantly lower (0·8 vs. 5·7, respectively; P  <   0·001), with better tolerability and significantly higher subject satisfaction regarding convenience and outcome. Conclusions: Daylight‐mediated PDT was not inferior in efficacy to Metvix c‐PDT (mild AK response rate), better tolerated, nearly painless and more convenient for patients. Abstract : What's already known about this topic? Methyl aminolevulinate conventional photodynamic therapy (MAL c‐PDT) is effective for treating actinic keratosis (AK), but may be a painful, inconvenient procedure. Daylight PDT (DL‐PDT) has shown good efficacy and safety results compared with c‐PDT in a previous randomized, controlled, exploratory trial. What does this study add? This study confirms previous findings that DL‐PDT can be considered as an effective, safe and convenient alternative for the treatment of facial/scalp AK. This is the first study showing a high maintenance of complete lesion response 6 months after one treatment.